Analysing the Impact of Land Use and Land Cover Changes on Ecosystem Service Values in Tangail Municipality, Bangladesh - Omi, Amrin Zaman; Reza, Farhadur (Journal of Sustainability and Environmental Management, 2024)
In the last few decades, rapid urbanisation has led to Land Use Land Cover (LULC) change, which has had a significant impact on the environment, ecosystem and its key goods and services around the globe. Ecosystem Service (ES) provides a wide range of benefits and advantages to communities and local economies. Land Use and Land Cover (LULC) changes have led to rapid alterations in composition, structure, and ecosystem functions, thereby reducing their capacity to provide essential services. Economic evaluation of ecosystem services is very crucial. Ecosystem Service Values (ESVs) are not given as much consideration in urban planning and policymaking, despite the fact that it is well known in the literature that urban ecosystems significantly contribute to human well-being in cities. Using ArcGIS 10.8.1, the LULC changes were computed for Tangail municipality between 2005 and 2023, based on LULC data computed from the Landsat imagery. The Benefits Transfer Approach (BTM) is used to calculate the changes in ESV associated with LULC changes. The research aims to analyse LULC change and assess its impact on ESV at the municipal level, providing a better understanding of how spatial patterns affect ESV. The results show a continuous reduction in ESV during the study periods. Between 2005 and 2023, due to the increase in built-up area, the area increased by about 46.66%. The ESV in Tangail Municipality has decreased from 3.02 million USD to 1.63 million USD during the same period. This study provides valuable insights that can aid in managing land resources and developing plans to mitigate the decline in ESV, ensuring sustainability and long-term ecosystem conservation at the municipal level.